The 'known' genetic potential for microbial communities to degrade organic phosphorus is reduced in low‐pH soils. Issue 4 (16th April 2017) - Lidbury, Ian D. E. A.; Fraser, Tandra; Murphy, Andrew R. J.; Scanlan, David J.; Bending, Gary D.; Jones, Alexandra M. E.; Moore, Jonathan D.; Goodall, Andrew; Tibbett, Mark; Hammond, John P.; Wellington, Elizabeth M. H.
Abstract: In soil, bioavailable inorganic orthophosphate is found at low concentrations and thus limits biological growth. To overcome this phosphorus scarcity, plants and bacteria secrete numerous enzymes, namely acid and alkaline phosphatases, which cleave orthophosphate from various organic phosphorus substrates. Using profile hidden Markov modeling approaches, we investigated the abundance of various non specific phosphatases, both acid and alkaline, in metagenomes retrieved from soils with contrasting pH regimes. This analysis uncovered a marked reduction in the abundance and diversity of various alkaline phosphatases in low‐pH soils that was not counterbalanced by an increase in acid phosphatases. Furthermore, it was also discovered that only half of the bacterial strains from different phyla deposited in the Integrated Microbial Genomes database harbor alkaline phosphatases. Taken together, our data suggests that these 'phosphatase lacking' isolates likely increase in low‐pH soils and future research should ascertain how these bacteria overcome phosphorus scarcity. Abstract : Phosphorus (P) is an essential element for all living organisms. Soil‐dwelling microorganisms are beneficial to plants as they can remineralize unavailable organic P, thus acting as biofertilizers. Our analyses revealed a significant reduction in the abundance of promiscuous organic P cleaving phosphatases in low‐pH soils, suggesting a potential reduction in their ability to remineralize P.